2013
DOI: 10.2174/1381612811319180015
|View full text |Cite
|
Sign up to set email alerts
|

An Update of Radiolabeled Bombesin Analogs for Gastrin-Releasing Peptide Receptor Targeting

Abstract: Prostate cancer is a critical public health problem in USA and Europe. New non-invasive imaging methods are urgently needed, due to the low accuracy and specificity of current screen methods and the desire of localizing primary prostate cancer and bone metastasis. Positron Emission Tomography (PET) and Single Photon Emission Computed Tomography (SPECT) are the non-invasive and sensitive imaging methods which have been widely used for diagnosing diseases in the clinic. Lack of suitable radiotracers is the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 0 publications
0
49
0
Order By: Relevance
“…The first-generation radiopeptides developed for such purposes were GRPR agonists derived from C-terminal fragments of the amphibian tetradecapeptide bombesin (BBN) (7)(8)(9)(10)(11)(12) or the respective human 27mer peptide GRP (13)(14)(15). The use of resulting radioligands in humans was soon linked to undesirable effects after agonist-induced GRPR activation (16).…”
mentioning
confidence: 99%
“…The first-generation radiopeptides developed for such purposes were GRPR agonists derived from C-terminal fragments of the amphibian tetradecapeptide bombesin (BBN) (7)(8)(9)(10)(11)(12) or the respective human 27mer peptide GRP (13)(14)(15). The use of resulting radioligands in humans was soon linked to undesirable effects after agonist-induced GRPR activation (16).…”
mentioning
confidence: 99%
“…After the successful use of radiolabeled somatostatin peptide analogs in neuroendocrine tumors for nuclear imaging and therapy (5,6), multiple radiolabeled GRPR radioligands have been synthesized and studied in preclinical as well as in clinical studies, mostly in prostate cancer patients. Examples of such peptide analogs include AMBA, the Demobesin series, and MP2653 (7)(8)(9)(10)(11). Recent studies have shown a preference for GRPR antagonists compared with GRPR agonists (12,13).…”
mentioning
confidence: 99%
“…The peptidic part of NeoBOMB1, however, is based on a different GRPR antagonist first described by Heimbrook et al (17) and generated by modification of the C-terminal Leu 13 -Met 14 -NH 2 and the replacement of Asn 6 by DPhe 6 of native bombesin (6)(7)(8)(9)(10)(11)(12)(13)(14). NeoBOMB1 was chosen for further studies because of its improved affinity for the GRPR (18,19).…”
mentioning
confidence: 99%
“…In this review, we discuss the preclinical and clinical work already done or under evaluation for the use of gastrin-releasing peptide receptors (GRPRs) as targets for the imaging of PC, with a focus on the development of PET tracers for the imaging of GRPRpositive tumors. Comprehensive recent reviews have discussed tracers for use in SPECT and therapy (2,3).…”
mentioning
confidence: 99%